Synthesis and FTIR spectroscopic investigation of the UV curing kinetics of telechelic urethane methacrylate crosslinkers based on the renewable resource-cardanol - Rekha, N.; Asha, S. K. (Journal of Applied Polymer Science, 2008)
UV curable telechelic urethane-methacrylate crosslinkers based on the natural resource-cardanol was synthesized in a one pot synthetic step involving end capping of isophorone diisocyanate with one equivalent of hydroxyethyl methacrylate followed by condensation with cardanol. The structures of the resins were characterized by H-1 and C-13 NMR, fourier transform infrared (FTIR) and Matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) spectroscopies and size exclusion chromatography (SEC). The curing process and double bond conversion in presence of 2,2-diethoxy acetophenone as photo-initiator upon UV irradiation was followed by Fourier transform infrared spectroscopy. These hydrogen bonded crosslinkers based on cardanol and its derivatives had higher double bond conversion when compared to a nonhydrogen bonding standard such as hexanediol diacrylate (HDDA) under identical conditions. The temperature effects on the hydrogen bonding were investigated, and a decrease in the extent of double bond conversion with increase in temperature was observed for the telechelic urethane-methacrylate crosslinkers whereas a steady increase in the curing rate was observed for HDDA. This gives direct indication of the influence of hydrogen bonding on the curing process. (C) 2008 Wiley Periodicals, Inc.
Keywords: Cardanol; hydrogen bonding; infrared spectroscopy; renewable resource; UV curing

Solvent-induced self-assembly in cardanol-based urethane methacrylate comb polymers - Rekha, N.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2009)
We report side chain urethane-methacrylate comb polymers based on the renewable resource cardanol and its saturated analogue 3-pentadecyl phenol and their self-assembly into pores, spheres, vesicles, tubes, and so forth. The monomers were synthesized in one pot by coupling 1 equiv. of isophorone diisocyanate with 1 equiv. of cardanol/pentadecyl phenol followed by coupling with 1 equiv. of hydroxyethyl methacrylate. They were polymerized free radically using benzoyl peroxide as the initiator and were characterized by NMR and FTIR, and their molecular weights were determined by gel permeation chromatography. The unique polymer design had sites for self-organization via hydrogen bonding of the side chain urethane units, pi-pi stacking interactions of the aromatic units as well as interdigitation of the long C(15) alkyl side chains in the polymer. The morphologies of solvent cast polymer films were studied using microscopic techniques such as scanning electron microscopy, transmission electron microscopy, and atomic force microscopy. The polymers exhibited three-dimensional honeycomb morphology in CHCl(3), whereas in tetrahydrofuran, they formed spheres. The direct cardanol-derived polymer PCIH showed a tendency for multiple morphologies such as spheres and tubes in tetrahydrofuran. (C) 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 47: 2996-3009, 2009
Keywords: Morphology; polyurethanes; Renewable resources; self-organization